2020
DOI: 10.5114/pm.2020.97835
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of the neutrophil/lymphocyte ratio with cardiovascular risk markers in premenopausal and postmenopausal women

Abstract: Introduction Cardiovascular disease is more frequent in postmenopausal women. Atherosclerosis is associated with inflammation and the neutrophil/lymphocyte ratio (NLR) is a marker of inflammation whose behavior in postmenopause is unknown. Aim of the study To know the relationship of the NLR with cardiovascular risk markers in premenopausal and postmenopausal women. Material and methods Premenopausal and postmenopausal women were studied, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…These two latter studies did not investigate the extent of stenosis or the carotid wall thickness. The few studies exploring the association between NLR and cIMT reported conflicting results 22–29 . Accordingly, some of them found an independent association between NLR and cIMT, 22–26 whereas this association was not observed in other studies 27–29 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These two latter studies did not investigate the extent of stenosis or the carotid wall thickness. The few studies exploring the association between NLR and cIMT reported conflicting results 22–29 . Accordingly, some of them found an independent association between NLR and cIMT, 22–26 whereas this association was not observed in other studies 27–29 .…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] Accordingly, some of them found an independent association between NLR and cIMT, [22][23][24][25][26] whereas this association was not observed in other studies. [27][28][29] Also, in a retrospective study, in patients with ischemic stroke, NRL was found to be a significant predictor of the cIMT in men but not in women. 23 These studies were conducted on small patient groups and involved very heterogeneous populations in terms of cardiovascular risk (ranging from apparently lower cardiovascular risk, 27 up to higher risk populations 22,23,25 ), type of IMT measure, baseline IMT and NLR values (Table S5).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations